Comparative study of thermogravimetric analysis among four microalgae species: Thermal characterization for bioenergy applications - Bento, Nicholas Alexandre Berger; Cosme, Lyon Lopes; Bacelos, Marcelo Silveira; Porto, Paulo Sérgio da Silva (Latin American Journal of Energy Research, 2025)
The energy exploitation of microalgae has attracted increasing interest due to their rapid growth, high lipid content, and CO₂ capture potential, making them a sustainable alternative to fossil fuels. However, variations in the proportions of lipids, proteins, carbohydrates, and ash in microalgae can influence the production of bio-oil, synthesis gas, and biochar. To highlight promising applications of specific species, thermogravimetric analyses play a fundamental role. Therefore, this research compares the thermal degradation of four microalgae species (Nannochloropsis oculata, Tetraselmis chuii, Phaeodactylum tricornutum, and Isochrysis galbana) using thermogravimetric analysis. Dried samples were subjected to tests in an inert nitrogen atmosphere, in platinum crucibles, with an initial mass of approximately 15 mg, heating from 25 to 800 °C and a rate of 10 °C/min. Based on the TGA and DTG curves, the initial temperature (Tonset), maximum degradation rate (Tmax), end of the main decomposition stage (Toffset), and final residue were determined. The results indicated similar profiles, with three degradation stages, but relevant differences between species. Nannochloropsis oculata showed the most intense DTG peak, indicating a greater release of volatiles, while Phaeodactylum tricornutum exhibited lower degradation intensity and a higher final residue (45.7%), suggesting a higher ash content. The species Tetraselmis chuii and Isochrysis galbana showed intermediate behavior. Despite the similarities in the decomposition pattern, the variations in thermal parameters indicate significant compositional differences, which can directly impact the thermochemical conversion potential. This reinforces the importance of TGA/DTG as a tool for selecting microalgal species for sustainable energy applications.